A CBF calculation of 1S0 Superfluidity in the Inner Crust of Neutron Stars - Pavlou, G.; Mavrommatis, E.; Moustakidis, Ch. C.; Clark, J. W. (HNPS Advances in Nuclear Physics, 2019)
Singlet S-wave superfluidity of dilute neutron matter in the inner crust of neutron stars is studied within the correlated BCS (Bardeen, Cooper, Schrieffer) method, taking into account both pairing and short-range correlations. First, the equation of state (EOS) of normal neutron matter is calculated within the correlated-basis-function (CBF) method in lowest cluster order using the Argonne V18 and V4′ potentials and Jastrow-type correlation functions. The 1S0 superfluid gap is then calculated with these potentials and correlation functions. The dependence of our results on the choice of the correlation functions is ana- lyzed and the role of higher-order cluster corrections is considered. The values obtained for the 1S0 gap within this simplified scheme are comparable to those from other, more elaborate, methods.